“Elaboración de un plan de mantenimiento para tractocamiones con motor detroit serie 60 línea CL120 para una empresa de transporte de carga” (2021)
In the present work is made a description of the freight transportation company, is diagnosed the actually failures in the maintenance execution, is made a criticality analysis to chose the most important equipment to develop a maintenance plan. Within the maintenance strategies found in theory, the most appropriate methodology is chosen. The maintenance plan is structured according to the chosen strategy within procedures, equipment data sheets, inspection forms. In the last part is made a finacial, ambiental and work safety analysis.